The performance of pistia stratiotes and eichornia crassipes for the heavy metal removal during backwash water from WASRA system - Firdaus, Ismail; Abdul Syukor, Abd Razak; Ali Zainal-Abidin, Mohamad Termizi; Muhammad Amirul Syafiq, Nasarudin; Suryati, Sulaiman (Penerbit UMP, 2024)
This study was conducted to determine the ability of Phytoremediation technology in treating groundwater contaminated with high heavy metal content of waste water, which is known as backwash water, using WASRA. Two types of aquatic plants have been used as agents for the treatment of wastewater; water hyacinth (Eichhornia crassipes) and water lettuce (Pistia stratiotes). To absorb heavy metals from the wastewater, two tanks were used for placing the plants. All analyses on wastewater are based on the Standard Procedures issued by American Public Health Association (APHA, 2017). The study of plant morphology is also conducted, where the study uses FESEM/EDX methods to determine the type of heavy metals found in these plant parts. These plants were divided into three parts which are leaves, stems, and roots. Based on experiments, different species of plants have the ability to remove metals at different levels of effectiveness. Thus, the two species, used as agents of phytoremediation are successful in removing heavy metals, with a removal rate of 50.79% to 88.49%. Pistia stratiotes precedes absorption rates of various heavy metals in high rates in the root part. In conclusion, phytoremediation technology has a very high potential in removing pollutants from water.